REVIEW OF INTER REGIONAL COOPERATION OF THE REGIONS AROUND MOUNT WILIS IN THE PERSPECTIVE OF STATUTORY REGULATIONS - Widya Lestari; Aulia Buana; Mila Wijayanti; Wiwandari Handayani (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2020)
Interregional cooperation is an important consequence of the implementation of decentralization and regional autonomy policy in Indonesia. Cooperation is the government’s effort to overcome the limitedness and to optimize their potentials in order to implement regional development efficiently and effectively to realize society welfare. The cooperation effort is done by six regencies (Tulungagung, Trenggalek, Ponorogo, Madiun, Nganjuk, and Kediri) around Mount Wilis - East Java to be able to mutually strengthen the process of development. The study aimed to review the implementation of regional development cooperation of the regions around Mount Wilis from the perspective of applicable statutory regulations. The result of review was used to find the opportunities and challenges in the implementation of interregional cooperation of the regions around Mount Wilis. The study used content analysis with descriptive qualitative approach to elaborate how the context of interregional cooperation according to statutory regulations was articulated in the cooperation performed. From the result of review, were found some opportunities and challenges in the implementation of interregional cooperation of the regions around Mount Wilis. The commitment of the regional governments of the six regencies, the Government of East Java, and the Central Government was an opportunity for cooperation. While the challenges faced were the implementation of institutional context and cooperation funding. The opportunity and challenge findings are expected to be a material for evaluation of implementation of interregional cooperation of the regions around Mount Wilis for future improvement of cooperation